Closed to reason: time for accountability for the International Narcotic Control Board - Small Dan; Drucker Ernest (BMC, 2007)
Abstract For more than two decades, the International Narcotic Control Board (INCB) has tried to stop harm reduction and its HIV prevention programs. This posture is based on a fundamental misunderstanding of their responsibilities and of drug addiction itself - i.e. as a public health and clinical care matter made criminal by decree. A recent focal point for the Board's action has been rejecting the use of supervised injection facilities to reduce morbidity and mortality of drug injectors. They single out individual countries and attempt to bully them into rejecting such programs under the banner of the United Nations (falsely) and in the name of international treaties. Their unrelenting and unjustified badgering of signatories to the international treaties that established the INCB is not only unjustified; it is an affront to one of the core purposes of the Board itself: to ensure adequate medical supplies and safe use of controlled substances. The INCB's ill-conceived obsession with intravenousaddiction as a crime flies in the face of the medical view and policies of the World Health Organization and the universally endorsed principles of the General Assembly of the United Nations. The latest target of the INCB is North America's only supervised injection facility, Insite, located in the inner city of Vancouver, Canada. Using the power of their office to meddle in matters of public health for individual nations is without medical, scientific or legal justification. But, most importantly, it is a matter of lifeand death for these most marginalized of citizens. The empirical evidence remains that a significant portion of the continued growth of the AIDS pandemic is due to injecting drug use, and the INCB's intrusion will inevitably result in additional deaths due to preventable HIV infections and drug overdoses. So we are very pleased to call to our readers' attention to a recent report produced by the Canadian HIV/AIDS Legal Network and the International Harm Reduction Development Program (IHRD) joined by former United Nations Special Envoy for HIV/AIDS in Africa, the respected Canadian statesman Stephen Lewis. The full report, "Closed to Reason: The International Narcotics Control Board and HIV/AIDS" is attached along [see Additional file <supplr sid="S1">1</supplr>] with a Russian translation of the key findings of the authors [see Additional files <supplr sid="S2">2</supplr>] as well as Russian and Chinese translations of this abstract [see Additional <supplr sid="S3">3</supplr> and <supplr sid="S4">4</supplr>]. As the report makes very clear, the time to inject some accountability and reason into the INCB is now. <suppl id="S1"> Additional file 1 <text> Closed to Reason: The International Narcotics Control Board and HIV/AIDS. Report by J. Csete and D. Wolfe of the Canadian HIV/AIDS Legal Network; International Harm Reduction Development Program (IHRD); Open Society Institute (OSI); 2007:1-32. </text> <file name="1477-7517-4-13-S1.pdf"> Click here for file </file> </suppl> <suppl id="S2"> Additional file 2 <text> Closed to Reason: The International Narcotics Control Board and HIV/AIDS Key Findings. Russian translation of key findings of the above report. </text> <file name="1477-7517-4-13-S2.pdf"> Click here for file </file> </suppl> <suppl id="S3"> Additional file 3 <text> "Closed to Reason": Time for Accountability for the International Narcotic Control Board. Russian translation of abstract of the above editorial. </text> <file name="1477-7517-4-13-S3.pdf"> Click here for file </file> </suppl> <suppl id="S4"> Additional file 4 <text> "Closed to Reason": Time for accountability for the International Narcotic Control Board. Chinese translation of abstract of the above editorial. </text> <file name="1477-7517-4-13-S4.pdf"> Click here for file </file> </suppl> Howmany times must a man look up Before he can see the sky Yes and how many ears Must one man have Before he can hear people cry? Yes, and how many deaths Will it take till he knows That too many people have died? Bob Dylan